ANALISIS HUBUNGAN KUALITAS SUMBER DAYA MANUSIA DAN KUALITAS SISTEM AKUNTANSI KEUANGAN DAERAH DENGAN KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - - Subadriyah; Anita Rahayuningsih (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The problem of Civil Servants often do not match the quality that should be needed. Accountingdepartment sometimes stand by incompetent human resources that affect the quality of accountingsystem and the quality of local government financial reports. This study aims to investigate theinfluence of the quality of human resources, the quality of local financial accounting system, andthe quality of local government financial reports. This research is an explanatory research by using SEM with AMOS. The sample used is SKPD and PPKD namely leadership and the staff inthe accounting department of Jepara and Kudus with 94 samples of respondents. The resultsshowed that the presence of the quality of human resources proved that affect the quality of thelocal government financial reports significance 0.000 and Critical Ratio 2.511. The quality ohuman resources is also evident effect on the application of financial accounting system with acritical ratio 5.710 and 0.000 significance. While the effect on the quality of the quality ofaccounting system to local government financial reports showed significances 0 000 with CR2.464.Keywords: Quality of Human Resources, Quality of Accounting System and Quality of Local Government Financial Report.